Perancangan Fin-tube Surface Cleaning System Untuk Pembersihan Air-Cooled Heat Exchanger - Ijlal Syaifullah; Ratu Fenny Muldiani; Teguh Sasono (Jurnal Mekanik Terapan, 2023)
Maintenance cleaning of the outer surface of the fin-tube on air-cooled heat exchangers is essential to maintain optimal performance. Performance degradation occurs due to the accumulation of dust and impurities on the fin-tube surface, forming crusty deposits when exposed to water. Currently, manual cleaning using water spray takes 80 hours to cover the entire surface. To improve cleaning efficiency, an innovative design of a water flow system using pipes and nozzles was developed. The design was based on calculations using Bernoulli's law and simulations with Ansys Fluent. The design achieved sufficient working pressure and nozzle inlet velocity of 0,37 m/s for 648 nozzles to cover 18 fans. With this design, cleaning can be completed in 59 minutes, removing 2,40Ã—10-8 kg of dust per nozzle, covering a cleaning area of 0,75 m2. The cleaning system is manually operated in monthly stages, requiring a total cleaning time of 17,70 hours. Effective cleaning is achieved by ensuring the fans are not in operation during the cleaning process.